Travels of Karel Čapek. On the Role of the Imaginative Variation in the Letters from Various Parts of Europe - Skibska, Anna Maria (Bohemistyka, 2017)
In the article, I take into consideration a series of Karel Čapek’s letters, which deliver a charming and cheerful evidence of his travel experiences resulted from his visits in various parts of Europe. In order to unveil the Czech writer’s originality regarding the poetics of travelogue, I refer to a number of figures, which are to organize his peculiar epistolary idiom. Čapek’s style is, therefore, determined by irony which turns out to be streaked with subsequent rhetorical devices such as litotes, correction, and self-correction linked with elliptical presence of aposiopesis. What is more, the Czech writer invests in the so-called variant manner of writing, due to which his letters instead of the common travel knowledge provides the reader with descriptions concerning details: from the traditional point of view, they might be perceived as meaningless facts, however, in Čapek letters they are transformed into individual, unique, and exceptional events, which are to remain in the reader’s consciousness.